Case Report: Severe thrombocytopenia induced by adalimumab in rheumatoid arthritis: A case report and literature review - Liao, Tiantian; Li, Mengqing; Yuan, Tian; Hong, Qifu; Zeng, Yu; Yu, Dan; Yu, Qiong; Yu, Limei; Pu, Tao (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by persistent joint inflammation. In recent decades, biological agents such as anti-tumor necrosis factor-α (TNF-α) drugs have been applied in the treatment of RA and it achieved great improvement. The treatment has its side effects, but severe thrombocytopenia is very rare. In this case report we described the occurrence of severe thrombocytopenia in a patient with RA who was treated with adalimumab. Specially, the symptoms of the RA are not significantly improved by adalimumab treatment and severe thrombocytopenia it induced is resistant to treatment. After receiving four doses of adalimumab, the patient's platelet count dropped to 4×103 /μL. We halted adalimumab and administered glucocorticoids, interleukins, and platelet transfusion. On the sixth day, the platelet count rose to 52×103 /μL. Lab tests and bone marrow pictures were unremarkable. Patient was treated with prednisone for maintenance. On day 17, the platelet count declined to 12×103 /μL. We started the patient on methylprednisolone and recombinant human thrombopoietin (rh-TPO), but the effect was not significant. On day 25, intravenous immune globulin (IVIG) was applied in place of the rh-TPO. On 29th day, the patient's platelets returned to normal. We summarized the existing literature on thrombocytopenia induced by anti-TNF-α drugs. This case suggested immunoglobulins could be considered for the treatment of refractory thrombocytopenia.